Attitudes towards homosexual and lesbians among Puerto Rican Public Health graduate students - González-Guzmán, Miriam; Santos-Ortíz, María Del Carmen; Dávila-Torres, René R.; Toro-Alonso, José (Puerto Rico Health Sciences Journal, 2007)
The objective of this study is to identify the attitude toward the homosexuals and lesbians among graduate students of General Public Health and Health Education Program at School of Public Health, Medical Sciences Campus of the University of Puerto Rico. A descriptive- 92 graduate students of the correlational design was used to carry out the study participated in the study General Public Health and Health Education programs. The data collection was collected through a selfadministered questionnaire. Descriptive and inferential statistics (Chi-square and t-test student) were used to data analysis. The 82.6% of the participants had a prejudiced attitude toward the homosexuals and the lesbians. The 79.3% presented a low distance level. There is a significant association among the social distance, homosexual and lesbian educational exposure and the years of studies. To develop appropriate strategies to foment the acceptance and eliminate the prejudice toward the homosexuals and lesbians in the participants, what will impact in a better way of providing quality health services.